Study of dental calculus in archaeological populations from northern Chile - Arriaza, Bernardo Tomás; Huamán, Luis; Villanueva, Fiorella; Tornero, Roxana; Standen, Vivien; Aravena, Natalia (Universidad Católica del Norte, Instituto de Investigaciones Arqueológicas y Museo, 2019)
Dental calculus and dental pathologies of 40 adults from 4 archaeological sites from the coastand valley of northern Chile were studied: MO 1/6, PLM-4, AZ-8 and CAM-9, analyzing 10individuals per site. In all of the dental calculus analyzed, phytolith and starches were found,except on the Late Archaic MO 1/6 site, which although did not present starch did presentphytoliths. These results are consistent with the macroscopical observation, where individualsbelonging to MO 1/6 site do not present dental cavities and generally have better dental healththan those individuals from the Late Intermediate and Late Period, both valley and the coastassociated with a mixed diet. Furthermore, a good concordance between grave goods plants andthe identified varieties in the dental calculus was observed in individuals from Late Intermediateand Late period sites.